Productivity, Impact, and Collaboration Patterns in Indian Nanocellulose Research for Biomedical Applications: A Bibliometric Perspective - Madhu, S; Pradeep, H K; Chandragirivar, Pratiksha C; Damani, Mohammad Yosuf Malik; Anusha, B N (Information Research Communications, 2026)
Background/Aim This study presents a bibliometric analysis of Indian research on nanocellulose for biomedical applications based on 692 Scopus-indexed publications produced between 2010 and 2025. Methodology Data were retrieved from the Scopus database and analysed using key bibliometric indicators, including Total Publications (TP), Total Citations (TC), Citations Per Paper (CPP), authorship patterns, and institutional productivity. Microsoft Excel was used for statistical analysis, while VOSviewer visualised thematic structures and collaboration networks. Results The 692 publications accumulated 23,812 citations (CPP 34.41). While 2010–2018 contributed 13.29% of output, it received 9,333 citations, indicating strong foundational influence. Peak productivity occurred in 2025 (21.53%). Journal articles (46.10%) were the primary output, but review papers (25.00%) attracted the highest citations. Thomas P. Sabu was the most productive author, and Mahatma Gandhi University, Kerala, led in institutional productivity. Discussion Keyword mapping revealed major clusters around nanocellulose materials, characterisation techniques, and biomedical applications such as drug delivery, tissue engineering, and wound healing. Conclusion The analysis identifies significant contributors and thematic hotspots, providing a structured overview to inform subsequent inquiries and policy-level interventions in this evolving domain.
Keywords: Bibliometric Analysis; Biomedical Application; India; Nanocellulose; Research Productivity; Scientometric.